2019
DOI: 10.1167/iovs.18-24776
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Retinopathy of Prematurity and Ocular Growth

Abstract: The purpose of this study was to prospectively investigate the association between retinopathy of prematurity (ROP) and ocular growth in premature infants during the earliest weeks of life. METHODS. Premature infants in the national ROP screening program were recruited and examined at 1-or 2-week intervals between 30 and 38 weeks of postmenstrual age. One hundred infants with gestational age (GA) between 24 and 35 weeks (30.04 þ 2.13), and birth weight (BW) between 550 and 2060 g (1251.45 þ 317.19) were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…16 Kardaras stated that a preterm infant with ROP has a slower growth rate than a preterm infant without it: 0.11 mm/week vs 0.24mm/week, during weeks 30 to 38 gestational age. 17 So these eyes grow slower, and Laws observed that the more severe the ROP, the smaller the axial length. 21 This was confirmed by Özdemir, who also described a shorter axial length in ROP infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Kardaras stated that a preterm infant with ROP has a slower growth rate than a preterm infant without it: 0.11 mm/week vs 0.24mm/week, during weeks 30 to 38 gestational age. 17 So these eyes grow slower, and Laws observed that the more severe the ROP, the smaller the axial length. 21 This was confirmed by Özdemir, who also described a shorter axial length in ROP infants.…”
Section: Discussionmentioning
confidence: 99%
“…The standard deviation values were obtained by personal communication. 17 Axer-Siegel investigated into whether in vitro fertilization would have an effect on axial length growth. As it did not have an effect, we included both the IVF and normally conceived children.…”
Section: B Critical Appraisal Of the Literaturementioning
confidence: 99%
“…LBW and prematurity are both associated with altered ocular morphologic development leading to several unique ocular sequelae in childhood. Former preterm LBW children have altered postnatal corneal thickness [1][2][3] and increased corneal steepness [4][5][6][7][8], smaller anterior chamber depth [4,6], increased lens thickness [4], and smaller axial length [5,8]. Especially anterior segment alterations may persist until adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…There are few reports analyzing corneal thickness in former preterm LBW children with or without Retinopathy of Prematurity (ROP) while the long-term effects up to adulthood are hardly understood. Different studies observed an increased CCT in preterm newborns compared to full-term newborns [1][2][3]10], followed by a longitudinal thinning [11]. Others detected that birth weight (BW) is negatively correlated with CCT [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation